Metodologias Ativas no Ensino de Sistemas Lineares no Ensino Fundamental. - CECILIA MARTINEZ VELHO (2023)
The central idea of this work was to analyze the active methodologies theme, their applications in the classroom, their objectives and present some related examples. The concepts of active methodologies were applied to a specific theme of elementary education, namely Matrices and Linear Systems. We elaborated a didactic sequence with the application of some active methodologies in linear systems activities for elementary education, such as challenges with figures (pictorial language), games with Cartesian planes, problem-solving with linear systems using algebraic language, and geometric representation with the aid of Geogebra software. Upon quickly searching the Profmat website for dissertations related to active methodologies, we noticed that there are 18 dissertations containing "Active Methodologies" and 5 dissertations containing "Active Methodology" in their titles, totaling 6,608 records as of September 3, 2022. Currently, this theme is constantly addressed in technical guidelines offered by the Education Department of Araçatuba - SP and in the training sessions offered by the Education Secretary of the State of São Paulo. Thus, we perceive that although active methodologies are not something new, they have been widely used. This work was applied to a 9th-grade class of an elementary school in Araçatuba - SP, in the second quarter of 2022, but we could not conclude the results, as during the application there was a Covid-19 outbreak, and many students were absent, hindering the sequence and the results.